ORGANOLEPTIC AND pH ASSESSMENTS ON BAUNG FISH (Mystus nemurus)WITH DIFFERENT MORTALITY PROCESS - Fadhlami, Putri Insani; karnila, Rahman; Edison, Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the different mortality process of baung fish that the different mortality process consisted of A1 (dead flounder) and A2 (dead pricker in Medulla oblongata). The assessment of the different ways to fish mortality consisted of organoleptic (eyes, gills, and odors) and pH.The assessment were conducted every 4 hours and the last assessment 12 hours were obtained organoleptic and pH A1 and A2 respectively, eyes 4.6, 5.3, gills 4.3, 5.3, odors 3.3, 4.3, and pH 4.6, 5.3. Based on the results, A1 (dead flounder) had lower organoleptic and pH assessments than A2 (dead pricker in Medulla oblongata).Keywords: Baung fish, Medulla oblongata, mortality process, organoleptic.